PENERAPAN APLIKASI UJIAN SEKOLAH BERBASIS ANDROID PADA SMP AL QOLAM KOTAAGUNG KABUPATEN TANGGAMUS - Kurniawan, Rolla (JECE (Journal of Ethics and Character Education), 2023)
Examination is one of the curriculum implementation activities that cannot be separated from one another. This school exam is usually carried out using paper with a written work system and usually there are types of questions, namely multiple choice and essays. AL QOLAM Middle School is a middle-level educational institution located on Jl. Soekarno Hatta Islamic Center, Kotaagung District, currently the school exam system such as midterm exams and final semester exams conducted at Al Qolam Middle School is still manual, namely using paper so it is not efficient in paper use , besides that the teachers will increase working hours to correct student exam results, then when the exam is carried out there will be a commotion because some students are cheating. To overcome these problems, we need an Android-based online exam application design. By maximizing the android mobile phones owned by students, online exams can use existing mobile phones in students, so that problems during exams can be resolved. the results of this study are that it can make it easier for students to do exercises and exams, especially during this covid pandemic. so students can still take exams and study at home